INVESTIGATING THE HOLISTIC MANAGEMENT IN INCREASING GRADUATES' COMPETENCE IN MADRASA BASED ON PESANTREN - Sanjani, M. Aqil Fahmi; Ridlo, Muhammad Husnur; Yanti, Lismei Sinti (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
This research aims to analyze and evaluate the effectiveness of Islamic boarding school-based school management in improving the quality of graduates. The quality of graduates is the outcome of the educational process that can determine the sustainability of an educational institution in the long run. The research focuses on identifying management strategies applied in the context of pesantren, measuring their impact on students' academic and non-academic achievements, and evaluating the educational governance within the pesantren environment. Through a descriptive qualitative approach with a case study, this research aims to contribute to a deeper understanding of the role of Islamic boarding school-based school management in shaping graduates with excellent quality and competitiveness. The research findings indicate that the holistic management impact on improving graduates' competence is achieved through the establishment of quality standards and pesantren-based quality control.